Unusual case of congenital fistula between external auditory canal and nasopharynx - Mandal, Manit M.; Panchal, Ajay J.; Kher, Shanu B.; Dudhani, Harsh G.; Shah, Vidhi D. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Defects in the development in the neck area of the embryo result in branchial cleft anomalies. Various first branchial cleft anomalies are described in literature including preauricular sinuses, cysts and collaural fistula. In our case study, we document a very unusual case of fistula between floor of external auditory canal and nasopharynx. Such patient requires thorough evaluation and step-wise approach to treat. After clinical examination and radiological evaluation, surgically the fistula was excised in toto via external approach using Modified Blair’s incision. In our case, fistulous tract was running from external auditory canal to nasopharynx, running superior and medial to the trunk of facial nerve. No such case is found to be reported in literature after extensive search. Hence, it would be strongly advocated to keep this presentation in the differential diagnosis during evaluation. Also, it is worth mentioning and recommending that a careful radiological examination is a must before approaching for surgery.